2013
DOI: 10.1088/1742-6596/409/1/012210
|View full text |Cite
|
Sign up to set email alerts
|

Neutron bursts associated with lightning cloud-to-ground discharges

Abstract: We present experimental results of the observations of the neutron flux birsts during the nearest thunderstorms in the years of 2009-2011. The neutrons were detected on the Yakutsk station by the standard neutron monitor 24-NM-64. The electric field during the thunderstorms were measured with the electrostatic fluxmeter near the monitor. The second electrostatic fluxmeter was located at 4 km from the monitor, on the building of the institute. Both fluxmeters allow us to register lightning discharges within a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…According to the long-term investigations of lightning events, which were carried out during the recent decades at the height of the Tien Shan mountain cosmic ray station, it was demonstrated that gamma-rays, electrons and neutrons can play a key role in the initiation and development of the atmospheric discharge [3,[10][11][12][13][14]. Similar results have been obtained in Aragats [15,16] and at other sites, both high-altitude [17] and sea-level [18,19] ones.…”
Section: Introductionsupporting
confidence: 55%
“…According to the long-term investigations of lightning events, which were carried out during the recent decades at the height of the Tien Shan mountain cosmic ray station, it was demonstrated that gamma-rays, electrons and neutrons can play a key role in the initiation and development of the atmospheric discharge [3,[10][11][12][13][14]. Similar results have been obtained in Aragats [15,16] and at other sites, both high-altitude [17] and sea-level [18,19] ones.…”
Section: Introductionsupporting
confidence: 55%
“…There may be short spikes inside the 2 min averaged count rate increases. Also, other authors indicate relations between atmospheric discharge and short time increases of neutrons (including thermal ones) at the same site (e.g., Babich et al, 2013;Kozlov et al, 2013;Martin & Alves, 2010;Starodubtsev et al, 2012;Tsuchiya et al, 2012). Recording time of each pulse, as well as anticoincidence between different channels of SEVAN, now in progress, may help in clarification.…”
Section: 1002/2016jd026439mentioning
confidence: 95%
“…The first evidences of a surplus neutron radiation at thunderstorm time have been reported in [2]. In recent years, some papers discuss the possibility of neutron generation in connection with powerful lightning discharges on the basis of experimental observations made at the mountain heights at Tien Shan [3,4], Aragats [5,6], Tibet [7], so as at the sea level in MSU [8] and Yakutsk [9]. Up to date, the different physical mechanisms were being discussed for explanation of thunderstorm related neutron production, but the nature this phenomenon still remains unknown.…”
Section: Introductionmentioning
confidence: 99%